Pelaksanaan Dan Evaluasi Penyuluhan Pertanian Pembuatan Pupuk Bokashi Di Desa Mangunrejo Magelang - Rijalul Haq; Dwi S. F. Astuti; Ranu Iskandar; Sunarsih Sunarsih; Yudiani Rina Kusuma (Abdimas Mandalika, 2021)
Abstract: Various studies have shown that bokashi  fertilizer is effective on the growth of crops grown by farmers. The purpose of this community service is to carry out and evaluate agricultural counseling on the manufacture of bokashi fertilizer in Mangunrejo Village. This community service procedure starts from (a) determining extension materials based on the RKTP, (b) compiling a synopsis, (c) making agricultural extension materials, (d) determining agricultural extension methods, (e) implementing agricultural extension, (f) setting evaluation objectives. ,(g) determine the evaluation method, (h) prepare evaluation instruments,(i) prove validity and reliability, (j) collect data, (k) tabulate data, (l) analyze data. The results of this service show that (a) the knowledge aspect of the training participants after participating in this training becomes aware with a percentage of 82.10%; (b) the attitude aspect of the training participants after attending this training became very agree with the percentage of 87.62%; (c) the skills aspect of the training participants after attending this training became skilled with a score of 80.27; and (d) this counseling was very effective with a percentage of 83.65%.Abstrak: Berbagai penelitian menunjukan bahwa pupuk bokashi efektif pada pertumbuhan tanaman yang ditanam petani. Tujuan pengabdian kepada masyarakat ini adalah untuk melaksanakan dan mengevaluasi penyuluhan pertanian pembuatan pupuk bokashi di Desa Mangunrejo. Prosedur pengabdian kepada masyarakat ini dimulai dari (a) menetapkan materi penyuluhan berdasarkan RKTP, (b) menyusun sinopsis, (c) membuat materi penyuluhan pertanian, (d) menetapkan metode penyuluhan pertanian, (e) melaksanakan penyuluhan pertanian, (f) menetapkan tujuan evaluasi, (g) menetapkan metode evaluasi, (h) mempersiapkan instrumen evaluasi, (i) pembuktian validitas dan reliabilitas, (j) pengumpulan data, (k) tabulasi data, (l) analisis data. Hasil pengabdian ini menunjukan bahwa (a) aspek pengetahuan peserta diklat setelah mengikuti pelatihan ini menjadi tahu dengan persentase 82,10%; (b) aspek sikap peserta diklat setelah mengikuti pelatihan ini menjadi sangat setuju dengan persentase 87,62%; (c) aspek keterampilan peserta diklat setelah mengikuti pelatihan ini menjadi terampil dengan persentase 80,27%; dan (d) penyuluhan ini sangat efektif denganpersentase 83,65%.